PENGARUH RASIO KEUANGAN TERHADAP KINERJA KEUANGAN PERBANKAN - Ade Isyana Hairunnisah (Universitas Riau Kepulauan, 2015)
Capital Adequacy Ratio, Non Performing Loan, Operating Expenses Operating Income Against and the Loan to Deposit Ratio, the banking performance is measured by Return on Assets. The approach used in the quantitative approach. The population in this study that the financial statements are published RB Banda Raya which includes Balance Sheet, Total Assets and Income Statement which contain financial ratio Capital Adequacy Ratio, Non Performing Loan, Operational Costs Against Operating income, Loan to Deposit Ratio, and Return On Assers. while the sample in this study was the period of the financial statements of RB Banda Raya, published quarterly period 2008-2012. The method used in this study is a multiple linear regression analysis to test the hypothesis that the t test and F test using SPSS 16. Results of this study indicate that the independent variable CAR, NPL, and LDR does not significantly affect the ROA because the significance value is above 0.05, while the independent variables significantly influence ROA, because the significance value less than 0.05. Based on R ² test showed that describes the ability of the independent variables on the dependent variable is the ROA of 59.4% while the remaining 40.6% is influenced by other factors beyond the independent factors used in this research.